The Authority of the Deposit Insurance Corporation as a Neo Lender of Last Resort: Prudential Principles and Risk Management from the Perspective of Monetary Constitutionalism - Asmara, Teguh Tresna Puja; Susanto, Mei; Adhihernawan, Muhammad Yoppy (Universitas Negeri Semarang, 2025)
Law No. 4 of 2023 on the Development and Strengthening of the Financial Sector has given a new authority to the Deposit Insurance Corporation (LPS) to place funds in order to handle bank liquidation problems. This authority makes LPS like a neo Lender of Last Resort (LoLR) institution that the central bank generally plays. The placement of funds by LPS can pose a great risk considering that the bank that receives the placement of funds falls into the category of banks under the restructuring of the Financial Services Authority (OJK) and does not meet the requirements of receiving loans or short-term liquidity financing from Bank Indonesia (BI). The research shows that: first, the authority of LPS as a neo LoLR in the form of fund placement can still be debated because it creates a double LoLR that is not in accordance with the principle of division and separation of powers. However, in a historical perspective, the authority to place LPS funds has existed since the mass economic crisis conditions caused by COVID-2019 with the issuance of PP No. 33 of 2020. Second, BI’s short-term liquidity loans or financing have more comprehensive requirements than the requirements for the placement of funds from LPS. These different requirements are very dangerous because they have the potential to ignore the character of predictability and knowledge in monetary constitutionalism. Even if the authority to place LPS funds exists, the implementation must apply the principles of prudence and risk management to anticipate potential unpredictable losses.